Making Tempe as a Learning Resource for Biotechnology Sub Material to Attract Entrepreneurial Interests of SMA Negeri 1 Tunjungan Blora - Eni Puji Rahayu (Contributions of Central Research Institute for Agriculture, 2023)
The rapid increase in the population of Indonesia in the era of globalization has caused many problems, one of which is the narrowing of job vacancies. Job opportunities with people looking for work more people looking for work. If someone has an interest in creating their own jobs (entrepreneurship) in accordance with the skills and knowledge they have, there is no need to rely on getting jobs from other people or government agencies. The population in this study were students of class XII in the Natural Sciences Program in the 2010/2011 academic year, consisting of 3 classes. The research was conducted in the even semester of the 2010/2011 academic year. The samples used were class XII IPA 1, XII IPA 2 and XII IPA 3. The research design used was the One Shot Case Study design. Data analysis was carried out using quantitative descriptive and percentage descriptive. The results showed that the interest in entrepreneurship in class XII IPA 1 was 82.86%, class XII IPA 2 was 88.25% and class XII IPA 3 was 80%. The high activity of students during learning activities is in line with good student learning outcomes, namely 100% of students achieving the completion criteria. Teachers show good to very good performance. It is known that both students and teachers are interested in the practical application of making tempeh. The conclusion from this research is that the application of practicum for making tempeh can attract students' interest in entrepreneurship, increase student activity and learning outcomes in learning the biotechnology sub-material.